2010
DOI: 10.1007/s11069-010-9511-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the vegetation destruction and recovery of Wenchuan earthquake using MODIS data

Abstract: The Ms 8.0 Wenchuan earthquake in 2008 has led to huge damage to land surface vegetation in northwest Sichuan, one of the typical ecological fragile regions in China. In this paper, the vegetation degradation by the earthquake and its recovery after the disaster are evaluated from analysis of MODIS Gross Primary Productivity (GPP) time series products and other ancillary GIS data. The results suggest that local vegetation GPP after the earthquake in the heavy afflicted area has decreased by 22%. The local vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…According to our study, herb areas such as meadows indicated the best vegetation recovery and they recovered better than woody plants. This confirms Liu's conclusions [19]. After Wenchuan earthquake, there has been sufficient precipitation for undersized vegetation (such as shrubs and herbs) under damaged trees which then became healthier [19].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…According to our study, herb areas such as meadows indicated the best vegetation recovery and they recovered better than woody plants. This confirms Liu's conclusions [19]. After Wenchuan earthquake, there has been sufficient precipitation for undersized vegetation (such as shrubs and herbs) under damaged trees which then became healthier [19].…”
Section: Discussionsupporting
confidence: 77%
“…Relative variables are often used to detect vegetation change and express vegetation information in remote sensing analysis and are categorized as the Normalized Differential Vegetation Index (NDVI) [15,16,18], Fractional Vegetation Coverage (FVC) [17], vegetation cover index [14,18], Gross Primary Productivity (GPP) [19], etc. There are two types of methods for extracting vegetation damage: one is to use a change detection threshold [15,16], and the other is to employ image classification [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, scientists are recognizing that natural disturbances, such as hurricanes, mudslides and floods, play an important role in the distribution of tropical vegetation, and that many assumptions concerning the relative importance of natural disasters warrant re-examination [18][19][20][21]. Vegetation indices (VI) derived from satellite images have long been used in remote sensing for monitoring vegetation changes and other related changes in land use.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported vegetation recovery after the earthquake. Liu et al monitored the early vegetation recovery within two months of the earthquake using MODIS GPP time-series products [12]. Lu et al (2012) used a time series of Landsat TM imagery to quantitatively assess the vegetation damage and monitor the vegetation recovery process after the earthquake and its associated secondary disasters [13].…”
Section: Introductionmentioning
confidence: 99%